“It actually helped”: students’ perceptions of feedback helpfulness prior to and following a teacher professional learning intervention - Brooks, Cameron; Burton, Rochelle; Van der Kleij, Fabienne; Ablaza, Christine; Carroll, Annemaree; Hattie, John; Salinas, Jaime Garcia (Frontiers in Education, 2024)
This study investigated the effects of a teacher professional learning intervention, underpinned by a student-centred model of feedback, on student perceptions of feedback helpfulness. The study was conducted in the context of primary education English writing in Queensland, Australia. No overall differences in feedback perceptions of students in 13 intervention and 9 comparison schools were identified following the intervention. However, more detailed analyses revealed significantly greater increases in perceived helpfulness among intervention group students for six feedback strategies. This suggests the intervention changed teachers’ feedback practices, enhancing student perceptions of feedback helpfulness. Student focus group data provided valuable qualitative insights into student feedback perceptions. Overall findings highlight the interrelatedness between feedback strategies across the feedback cycle for enhancing student learning.